Genetic diversity and marker–trait association analysis for agronomic traits in Aconitum carmichaelii Debeaux - Ma Yu; Ling-Li Cao; Yu-Xia Yang; Ling-Liang Guan; Lu-Lu Gou; Xiao-Yan Shu; Jing Huang; Dan Liu; Hong Zhang; Da-Bin Hou (Biotechnology & Biotechnological Equipment, 2017)
The root of Aconitum carmichaelii Debeaux is used in Oriental folk medicine, but its cultivation is very labour intensive. Therefore, it is important to dissect the genetic mechanism of agronomic traits to breed elite cultivars for commercial cultivation. We analyzed the genetic diversity of 126 genotypes of A. carmichaelii collected from the major productive regions in China based on 280 amplified fragment length polymorphism (AFLP) loci. The values of the coefficient of gene differentiation, Nei's gene diversity index, and Shannon's information index, and the results from a hierarchical analysis of molecular variance analysis indicated that there is more genetic variability within populations than between populations. Marker–trait association analyses were conducted under a general linear model without controlling for population structure, and under a relative kinship model. In total, 59 loci were identified under both models for plant height (PH), stem diameter (SD), lateral root number (LRN), fresh weight and dry weight of stem (FWS and DWS, respectively), fresh weight and dry weight of leaves per plant (FWL and DWL, respectively), and fresh weight (FWR) and dry weight of individual lateral roots (DWR). Thirty-eight loci were associated with two to eight traits. For example, P1M1-39 was associated with variations in DWR, DWS, FWS, SD, DWL, FWL, FWR and PH, and P1M1-14 was close to a locus associated with variations in DWR, DWS, FWS, DWL, FWL, PH, FWR and LRN. Loci associated with favourable traits should be combined in commercial varieties to improve the yield and quality of A. carmichaelii.